Developmental Lead Exposure and Prenatal Stress Result in Sex-Specific Reprograming of Adult Stress Physiology and Epigenetic Profiles in Brain. (21st February 2018) - Sobolewski, Marissa; Varma, Garima; Adams, Beth; Anderson, David W; Schneider, Jay S; Cory-Slechta, Deborah A
Abstract: Developmental exposure to lead (Pb) and prenatal stress (PS) both impair cognition, which could derive from their joint targeting of the hypothalamic-pituitary-adrenal axis and the brain mesocorticolimbic (MESO) system, including frontal cortex (FC) and hippocampus (HIPP). Glucocorticoids modulate both FC and HIPP function and associated mediation of cognitive and other behavioral functions. This study sought to determine whether developmental Pb ± PS exposures altered glucocorticoid-related epigenetic profiles in brain MESO regions in offspring of female mice exposed to 0 or 100 ppm Pb acetate drinking water from 2 mos prior to breeding until weaning, with half further exposed to prenatal restraint stress from gestational day 11–18. Overall, changes in females occured in response to Pb exposure. In males, however, Pb-induced neurotoxicity was modulated by PS. Changes in serum corticosterone levels were seen in males, while glucocorticoid receptor changes were seen in both sexes. In contrast, both Pb and PS broadly impacted brain DNA methyltransferases and binding proteins, particularly DNMT1, DNMT3a and methyl-CpG-binding protein 2, with patterns that differed by sex and brain regions. Specifically, in males, effects on FC epigenetic modifiers were primarily influenced by Pb, whereas extensive changes in HIPP were produced by PS. In females, Pb exposure and not PS primarily altered epigenetic modifiers in both FC and HIPP. Collectively, these findings indicate that epigenetic mechanisms may underlie associated neurotoxicity of Pb and of PS, particularly associated cognitive deficits. However, mechanisms by which this may occur will be different in males versus females.